Competition within a Cartel: League Conduct and Team Conduct in the Market for Baseball Player Services - Ferguson, Donald G.; Jones, J. C. H.; Stewart, Kenneth G. (The Review of Economics and Statistics, 2000)
A model of major league baseball is developed which distinguishes between league behavior and individual team behavior. The league is viewed as setting rules that restrict the team's willingness to pay and/or impose costs on the transfer of players between teams. Given these rules, teams then compete for player services. The model is estimated and tested. The evidence suggests that the restrictive effect of league rules on player salaries declined between 1986-1988 and 1989-1991, consistent with anecdotal evidence. Within the rules established by the league, however, teams appear to behave as competitive price-takers through the entire sample period.